Substance use, injection risk behaviors, and fentanyl-related overdose risk among a sample of PWID post-Hurricane Maria - Roberto Abadie; Manuel Cano; Patrick Habecker; Camila Gelpí-Acosta (BMC, 2022)
Abstract Background While natural disasters like hurricanes are increasingly common, their long-term effects on people who inject drugs are not well understood. Although brief in duration, natural disasters can radically transform risk environments, increasing substance use and drug-related harms. Methods Based on a study of people who inject drugs (PWID) and injection risk behaviors in rural Puerto Rico, the present study uses data from two different phases of the parent study. Data for 110 participants were collected from December 2015 to January 2017, soon before Hurricane Maria landed in September 2017; the 2019 phase, in the aftermath of the hurricane, included a total of 103 participants. The present study's main analyses used data from 66 PWID who participated in both the pre-Maria and post-Maria interviews (66 individuals measured at two time points, for a total of 132 observations), using mixed-effects binomial logistic regression to examine recent overdose experiences pre- and post-Maria. A separate descriptive analysis included all 103 participants from the 2019 interview. Results After Hurricane Maria, some declines in injection frequency were observed (the percentage of people reporting injecting monthly or less increased from 3.0% before Hurricane Maria to 22.7% after Hurricane Maria). However, fewer PWID reported using a new needle for most or all injections. In the pre-Maria interview, 10.6% of participants indicated they had experienced an overdose during the year of the interview and/or the calendar year prior, and this figure increased to 24.2% in the post-Maria interview. In the regression analysis, the odds of reporting an overdose during the interview year and/or calendar year prior were three times as high post-Maria, relative to pre-Maria (odds ratio 3.25, 95% confidence interval 1.06-9.97). Conclusion Substance use patterns, injection risk behaviors, and overdose episodes and deaths differed after Hurricane Maria, relative to before the hurricane, yet it is unclear to what extent these changes also reflect the simultaneous arrival of fentanyl. In preparation for future natural disasters, it is imperative to strengthen the health infrastructure by enhancing access and curbing barriers to syringe services programs and medications for opioid use disorder, particularly in rural or underserved locations.